Feasibility of Adjuvant Chemotherapy After Pelvic Exenteration for Gynecologic Malignancies. Issue 5 (1st June 2013) - Andikyan, Vaagn; Khoury-Collado, Fady; Sandadi, Samith; Tew, William P.; O'Cearbhaill, Roisin E.; Konner, Jason A.; Sonoda, Yukio; Barakat, Richard R.; Chi, Dennis S.; Abu-Rustum, Nadeem R.
Abstract : Objective: It is well documented that recurrence after pelvic exenteration remains high (up to 50%), and patients may require a prolonged period of recuperation following this aggressive surgery. We conducted a retrospective review to evaluate the feasibility of administering adjuvant chemotherapy after pelvic exenteration for gynecologic malignancies. Methods: We reviewed the medical records of patients with any gynecologic cancer who underwent exenterative surgery between January 2005 and February 2011 at our institution. Patients were referred for postexenteration adjuvant chemotherapy based on surgeon's discretion and/or presence of high-risk features: positive margins, positive lymph nodes, and/or lymphovascular space invasion. Suitability for chemotherapy was assessed by a gynecologic medical oncologist. Regimens consisted of 4 to 6 cycles of platinum-based doublet chemotherapy. Chemotherapy-related toxicities were assessed using the Common Terminology Criteria for Adverse Events version 4. Results: We identified 42 patients who underwent pelvic exenteration during the study period. Eleven (26%) were referred for adjuvant chemotherapy. Three (27%) of the 11 patients did not receive chemotherapy because of delayed postoperative recovery or physician choice. Seven (88%) of the remaining 8 patients completed all scheduled chemotherapy. Grade 2 toxicities or greater were documented in 6 patients (75%), the most common being neutropenia, neuropathy, and fatigue. Median follow-up time was 25 months (range, 6–56 months). The 3-year progression-free and overall survival rates of the 8 patients who received chemotherapy were 58% (95% confidence interval, 18%–84%) and 54% (95% confidence interval, 13%– 83%), respectively. Conclusions: The administration of adjuvant chemotherapy is feasible for a select group of patients after pelvic exenteration for gynecologic malignancies. Our results need to be interpreted with caution because of the small and heterogeneous cohort of patients included.